Optimal placement of PMUS considering SCADA measurements and fixed channel capacity by semidefinite programming - Manousakis, N.M; Korres, G.N (MedPower 2014, 2014)
This paper presents a semidefinite programming (SDP) formulation with binary decision variables, for the optimal placement of phasor measurement units (PMU), considering the existence of conventional measurements and the impact of limited channel capacity (OPP-LCC). The proposed problem minimizes a linear objective function subject to linear matrix inequality (LMI) observability constraints. Simulations, using a Matlab-based SDP software, are conducted on different IEEE systems to prove the validity of the proposed method.